The Role of Entrepreneurial Mindset, Digital Marketing Strategies, Social Capital, and Business Model Innovation in Enhancing Startup Growth in Indonesia - Tubalawony, Jacsy (West Science Interdisciplinary Studies, 2025)
This study investigates the role of entrepreneurial mindset, digital marketing strategies, social capital, and business model innovation in enhancing startup growth in Indonesia. Using a quantitative approach, data were collected from 150 startup founders and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The findings reveal that all four factors significantly contribute to startup growth. Entrepreneurial mindset and business model innovation show the strongest effects, followed by digital marketing strategies and social capital. The study highlights the importance of fostering an entrepreneurial mindset, leveraging digital marketing, cultivating social networks, and innovating business models to drive growth in the competitive Jakarta startup landscape. These results provide valuable insights for entrepreneurs, policymakers, and investors seeking to enhance startup performance in emerging economies.